Exolysin (ExlA) from Pseudomonas aeruginosa Punctures Holes into Target Membranes Using a Molten Globule Domain. Issue 16 (24th July 2020) - Bertrand, Quentin; Job, Viviana; Maillard, Antoine P.; Imbert, Lionel; Teulon, Jean-Marie; Favier, Adrien; Pellequer, Jean-Luc; Huber, Philippe; Attrée, Ina; Dessen, Andréa
Abstract: Bacteria employ several mechanisms, and most notably secretion systems, to translocate effectors from the cytoplasm to the extracellular environment or the cell surface. Pseudomonas aeruginosa widely employs secretion machineries such as the Type III Secretion System to support virulence and cytotoxicity. However, recently identified P. aeruginosa strains that do not express the Type III Secretion System have been shown to express ExlA, an exolysin translocated through a two-partner secretion system, and are the causative agents of severe lung hemorrhage. Sequence predictions of ExlA indicate filamentous hemagglutinin (FHA-2) domains as the prevalent features, followed by a C-terminal domain with no known homologs. In this work, we have addressed the mechanism employed by ExlA to target membrane bilayers by using NMR, small-angle X-ray scattering, atomic force microscopy, and cellular infection techniques. We show that the C-terminal domain of ExlA displays a "molten globule-like" fold that punctures small holes into membranes composed of negatively charged lipids, while other domains could play a lesser role in target recognition. In addition, epithelial cells infected with P. aeruginosa strains expressing different ExlA variants allow localization of the toxin to lipid rafts. ExlA homologs have been identified in numerous bacterial strains, indicating that lipid bilayer destruction is an effective strategy employed by bacteria to establish interactions with multiple hosts. Graphical abstract: Unlabelled Image Highlights: Exolysin (ExlA) is expressed by P. aeruginosa strains that lack the T3SS. ExlA is secreted by a TPSS and displays a C-terminal molten globule domain. The mechanism of ExlA toxicity involves perforation of negatively charged membranes. ExlA localization in infected cells highlights a functional link with lipid rafts.